Creating space(s) for growth a tech-generative research and development (R&D) center for climate-smart agriculture - Anastacio, Xyrille H.
It is projected that the Philippines, due to climate change, will experience a decline in agriculture productivity of 9-12% by 2050, posing risks to the country's food security and economy (Puhlin and Tapia, 2016). To improve the agricultural sector's competitiveness and resilience to climatic shocks, climate-smart agriculture (CSA) can be adopted, and approach that transforms agri-food systems based on three pillars: increasing farm productivity and incomes, enhancing the resilience of livelihoods and ecosystems, and reducing greenhouse gas emissions. CSA is a relatively new concept in the country thus, investments must be poured into nurturing its practices and technologies, including a research and development (R&D) facility. This study explores how the various CSA practices and technologies can be integrated architecturally in an R&D facility located at the Central Luzon State University (CLSU). Interviews with key persons from CLSU and the International Research Rice Institute (IRRI) were conducted to understand the concept of CSA further. A survey questionnaire was also distributed to CLSU students who use R&D facilities in the university to know their perspectives and spatial preferences. The data gathered from these methods, along with the data from related literature, precedent studies, and site and user/market analyses, were used in the project's succeeding conceptual and design development stages.